2008
DOI: 10.5194/angeo-26-1641-2008
|View full text |Cite
|
Sign up to set email alerts
|

Iterative inversion of global magnetospheric ion distributions using energetic neutral atom (ENA) images recorded by the NUADU/TC2 instrument

Abstract: Abstract.A method has been developed for extracting magnetospheric ion distributions from Energetic Neutral Atom (ENA) measurements made by the NUADU instrument on the TC-2 spacecraft. Based on a constrained linear inversion, this iterative technique is suitable for use in the case of an ENA image measurement, featuring a sharply peaked spatial distribution. The method allows for magnetospheric ion distributions to be extracted from a low-count ENA image recorded over a short integration time (5 min). The tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The ring current consists mainly of energetic ions and electrons that drift azimuthally in the magnetic field gradient in the inner magnetosphere at radial distances of about 2-7 Earth radii (R E ). The main enhancement in the storm-time ring current occurs at distances of L ~4 (C:son Brandt et al, 2002a;Lu et al, 2008) and is measured using the Dst (or SYM-H) index.…”
Section: Introductionmentioning
confidence: 99%
“…The ring current consists mainly of energetic ions and electrons that drift azimuthally in the magnetic field gradient in the inner magnetosphere at radial distances of about 2-7 Earth radii (R E ). The main enhancement in the storm-time ring current occurs at distances of L ~4 (C:son Brandt et al, 2002a;Lu et al, 2008) and is measured using the Dst (or SYM-H) index.…”
Section: Introductionmentioning
confidence: 99%
“…[42] More recently, a method customized for NUADU data, which during ring current disturbances feature spatially sharply peaked bright emissions, was developed to retrieve the parent ion distributions [Lu et al, 2008]. The ENA images utilized in this procedure are first cleaned to (1) remove effects due to solar photons, (2) balance statistically noise responses between different detectors, and (3) correct polar overlaps in the fields of view of certain detectors.…”
Section: Methods Of Ion Distribution Retrieval Customized For Nuadu Datamentioning
confidence: 99%
“…Section 4 provides an overview of classical methodologies used to retrieve ion distributions from ENA images. An account of a method recently developed [Lu et al, 2008] to retrieve ion distributions from data measured by NUADU under disturbed geomagnetic conditions is outlined in section 4.2 and described in detail in Appendices A and B. This method is used to derive ion distributions in the ring current recorded by NUADU between 2330 and 2400 UT, 21 January, 0030-0100 UT, 22 January, and 0100-0130 UT, 22 January 2005.…”
Section: Present Studymentioning
confidence: 99%
“…Initial investigations showed that the DeMajistre inversion method is not suitable to use when processing NUADU data as the solutions thereby obtained tend to oscillate, and even to present negative values. Also, the strong coefficient of constraint required to be employed can act to smooth the inverted ion flux distribution unduly and, thereby, compromise the correct recovery of the region of maximum ENA emission [Lu et al, 2008;McKenna-Lawlor et al, 2010]. To overcome these problems, a custom designed method was developed (section 2) to retrieve ion distributions for NUADU measurements based on a kappa model (whereas the DeMajistre method employs an exponent model).…”
Section: Analysis Of Nuadu/ena Datamentioning
confidence: 99%